PENGARUH PENGETAHUAN PERPAJAKAN, TINGKAT PENDIDIKAN, DAN SANKSI ADMINISTRASI TERHADAP KEPATUHAN WAJIB PAJAK DALAM MELAKUKAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN (Studi Kasus Pada Kantor Dinas Pendapatan Daerah Kabupaten Sleman) - Tika Wulandari; Suyanto Suyanto (Jurnal Akuntansi, 2014)
This study aims to determine the factors that influence compliance in land and building tax payments in the District Sleman.Variabel dependent adherence in this study were paying taxes. The independent variables in this study include knowledge of taxation, education, administrative sanctions. This study used a questionnaire for data collection. Sample research study is registered taxpayers in Revenue Kabupten Sleman. Analysis of research data using multiple linear regression. The results showed that the variable tax knowledge and administrative penalties positive significant effect on adherence Land And Building Tax payments while the education variable does not affect the compliance of land and building tax payments. Keywords: knowledge of taxation, education, administrative sanctions, Compliance.